Kriminalisasi Tanpa Batas: Mengurai Penyalahgunaan Kekuasaan dalam Legislasi Kodifikasi Hukum Pidana Modern - Zul Khaidir Kadir (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Criminalization in criminal law should function to limit actions that harm society legally and proportionally, but excessive criminalization can ignore the principles of justice and legality. A striking gap arises when the law is used not to protect rights, but to expand state control over individual freedom through repressive and multi-interpretable articles. This study uses a qualitative research method with a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study show that unlimited criminalization reflects an abuse of power that moves criminal law away from its protective function towards an instrument of repression that exacerbates inequality and weakens legal legitimacy. To return criminal law to its fair function, legislative reform is needed based on transparency, participation, and a non-penal approach that prevents state domination over individual rights.